2007
DOI: 10.1007/s00408-006-0117-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Continuous Positive Airway Pressure Therapy on Blood Pressure in Patients with Obstructive Sleep Apnea Hypopnea: A Meta-analysis of Randomized Controlled Trials

Abstract: Patients with untreated obstructive sleep apnea hypopnea (OSAH) are predisposed to developing hypertension, and therapy with continuous positive airway pressure (CPAP) may reduce blood pressure (BP). The purpose of this study was to assess the impact of CPAP therapy on BP in patients with OSAH. We performed a comprehensive literature search up to July 2006 [Medline, PubMed, EMBASE, Cochrane Database of Systematic Reviews (CDSR), Cochrane controlled trials register (CCTR), and Database of Abstract and Reviews o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
2
10

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(137 citation statements)
references
References 32 publications
6
119
2
10
Order By: Relevance
“…161 Overall, the net reduction in BP (Ϸ2 mm Hg) was significant but modest. A third meta-analysis 162 included randomized controlled trials that reported systolic and diastolic BPs before and after CPAP/control and noted modest (Ϸ1.5 mm Hg) decreases in both systolic BP (Pϭ0.23) and diastolic BP (Pϭ0.06). In 6 trials that evaluated more severe OSA (AHI Ͼ30), CPAP reduced systolic BP by Ϸ3 mm Hg (Pϭ0.10) and diastolic BP by 2 mm Hg (Pϭ0.05).…”
Section: Treatment Of Osa: Effects On Hypertensionmentioning
confidence: 99%
“…161 Overall, the net reduction in BP (Ϸ2 mm Hg) was significant but modest. A third meta-analysis 162 included randomized controlled trials that reported systolic and diastolic BPs before and after CPAP/control and noted modest (Ϸ1.5 mm Hg) decreases in both systolic BP (Pϭ0.23) and diastolic BP (Pϭ0.06). In 6 trials that evaluated more severe OSA (AHI Ͼ30), CPAP reduced systolic BP by Ϸ3 mm Hg (Pϭ0.10) and diastolic BP by 2 mm Hg (Pϭ0.05).…”
Section: Treatment Of Osa: Effects On Hypertensionmentioning
confidence: 99%
“…All point to a blood pressure reduction with the use of CPAP. Only one of them 62 did not show a beneficial effect of CPAP treatment on blood pressure control. However, when analyzed in only 52 . six studies with more severely ill patients (AHI > 30 events/ hour), the result showed reduction in systolic blood pressure by 3.3 mmHg and in diastolic blood pressure by 2.03 mmHg.…”
Section: Treatmentmentioning
confidence: 87%
“…Summarizing these findings, a systematic review 61 and four meta-analyses [62][63][64][65] assessing the impact of CPAP on blood pressure have been published in the past few years. All point to a blood pressure reduction with the use of CPAP.…”
Section: Treatmentmentioning
confidence: 99%
“…Ponieważ udowodniono związek otyłości i obturacyjnego bezdechu sennego, zaleca się powszechnie obniżenie masy ciała, choć niestety nie przeprowadzono kontrolowanych badań na szeroką skalę dotyczących tego zagadnienia [521]. Skuteczną metodę leczenia zmniejszającą nasilenie obturacyjnego bezdechu sennego jest zastosowanie ciągłego dodatniego ciśnienia w drogach oddechowych, jednak na podstawie dostępnych wyników 4 metaanaliz wykazano, że wpływ przedłużonej terapii ciągłym dodatnim ciśnieniem w drogach oddechowych pozwala jedynie na niewielkie obniżenie BP (1-2 mm Hg) [522][523][524][525]. Może to wynikać ze słabej współpracy pacjentów ze względu na złożoność procedury lub ograniczonego okresu obserwacji, chociaż w ostatnim badaniu, w którym czas obserwacji wynosił ponad 3 lata, nie stwierdzono różnic w wartościach BP czy intensywności stosowanego leczenia hipotensyjnego u osób z obturacyjnym bezdechem sennym, którzy kontynuowali lub zaprzestali terapii dodatnim ciśnieniem w drogach oddechowych [526].…”
Section: Obturacyjny Bezdech Sennyunclassified